Fishing in the same pool? export strengths and competitiveness of China and CESEE in the EU-15 Market - Maria Silgoner; Katharina Steiner; Julia Wörz; Christian Schitter (European Central Bank (ECB), 2013)
We investigate the impact of China as a global competitor on the trade performance of the ten Central, Eastern and Southeastern European EU Member States (CESEE-10) in the EU-15 market. The paper takes a comprehensive approach as we analyze export growth, export market shares, extensive and intensive margins and the dynamics in the number of joint trade links (Dynamic Trade Link Analysis) from 1995 to 2010. According to our findings, the most contested markets are those for capital goods and transport equipment. Overall, competition between CESEE-10 and China intensified as a result of their outstanding competitiveness and the continuous deepening of already existing trade relationships, while cutthroat competition has not materialized. While this suggests that the CESEE countries pursue a suitable export strategy, diversification of production toward promising new industries and markets remains essential, not least because the EU-15 market is projected to grow at a slower pace in the longer run.
Keywords: F14; F15; O57; 330; central; China; competitiveness; Eastern and Southeastern Europe; trade shift-share analysis